Annual preventive parasitological survey of students in Ternopil state medical university - Tsebryk, Sviatoslav; Pokryshko, Alina (Czech Republic, Karlovy Vary – Ukraine, Kyiv, 2018)
More than a third of the world's population is infected with worms (helminths). There are many different types, but the most common are soil-transmitted helminths (roundworm, whipworm and hookworm) and schistosomiasis which can negatively affect children’s health, nutrition and education.
Keywords: тези